Academic Internationalization, Global Public Goods and Global Commons Goods: New Challenges for the Universities - Rosell Aiquel, Rafael; Martin-Fiorino, Víctor; Caldera Ynfante, Jesús Enrique (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Higher Education must respond to global dynamics that cause profound transformations in the knowledge, interactions and life of people, communities and ecosystems. In critical environments, Universities need to learn to become agents of the future in the face of the challenges of producing global public goods and protecting the global commons. Education as a global common good and constructive interdependence are references to assume global challenges that go beyond the Nation State and require promoting internationalization as a requirement of adaptation and transformation for which higher education institutions are obliged.